TEACHERS' EXPECTATIONS AND MATHEMATICS COMPETENCE OF PRIMARY ONE LEARNERS: A COMPARATIVE STUDY OF BUSIRO AND LUUKA, UGANDA - Kisa, Sarah; Ejuu, Godfrey; Asiimwe, Joyce Ayikoru (African Journal of Education and Practice, 2020)
Purpose: Teacher expectations of their learners' competence has been seen as a key contributor to children's level of performance in a given subject area. However, in the case where teachers already feel their learners do not have the competence, can the children have a chance of doing any better? This study explored the primary one teachers' expectations of their learners' mathematics competence to ascertain the linkage between those expectations and the learners' performance in the identified mathematics competences. Methodology: The comparative study was conducted in Busiro North and Luuka North Counties in Uganda among primary one learners and teachers. A cross-sectional survey was used to collect data from 74 purposively selected primary one teachers and 296 randomly selected learners from 37 schools in Busiro North and 37 schools in Luuka North Counties respectively. Data collection tools used were questionnaires, learners' mathematics competence test and artefacts of learners' written work. Data analysis was done using the Statistical Package for the Social Sciences (SPSS). The t-test for independent groups was used to compare the learners' test scores, while Pearson r was used to establish the relationship between teachers' expectations and learner performance. Findings: Results showed significant relationships between teacher expectations and learners' performance for both Busiro and Luuka (r =0.711, r = 0.596). Teachers considered age of a learner; language used as medium of instruction; and having attended nursery school as important background factors that promote a P.1 learner's mathematics competence. Unique contribution to theory, practice and policy: The findings indicate a need for primary school teacher education courses to inform pre-service teachers about teacher expectations and their associated influence on learner performance. All teachers are urged to use strategies that encourage learners to meet teacher expectations. Teachers in urban areas ought to include more practical approaches to teaching mathematics in order to develop lasting and applicable skills in the learners.